Identification and Analysis of Long Non-coding RNAs in Leuciscus waleckii Adapted to Highly Alkaline Conditions - Zhao, Xue Fei; Liang, Li Qun; Liew, Hon Jung; Chang, Yu Mei; Sun, Bo; Wang, Shuang Yi; Mi, Bo Han; Zhang, Li Min (Frontiers in Physiology, 2021)
Leuciscus waleckii is a freshwater fish that is known to live in alkaline water at pH9.6 in Dali Lake, Inner Mongolia, China, but the physiological plasticity mechanism of this alkaline adaptability remains unclear. Transcriptional component analysis has shown a large number of genes involved in osmo-ionoregulation and arachidonic acid metabolism pathway expression changed significantly in the process of acid-base balance regulation under high alkaline stress. Therefore, this study was designed to investigate the mechanism of lncRNA in the process of high alkaline adaptation. Fish were challenged to 0 mM, 30 mM(pH9.44±0.08), and 50 mM (pH9.55±0.06) for 20 days. Gill and kidney tissues were collected for high throughput sequencing assays. A total of 159 million clean reads were obtained by high throughput sequencing and 41248 lncRNA transcripts were identified. Based on analysis of differential lncRNA transcript expression, a total of 5244 and 6571 lncRNA transcripts were found to be expressed differentially in the gills and kidneys, respectively. Both GO and KEGG of coding genes correlated to lncRNA expression patterns. GO analysis showed that a large number of lncRNAs are enriched in terms such as "transporter activity", "response to stimulus", and "binding". KEGG revealed that metabolism pathways were found to be significantly enriched. A random selection of 16 lncRNA transcripts for RT-qPCR verified that the results were consistent with the sequencing results. It was found that a large number of genes with the same expression pattern as those with significantly different expression of lncRNAs were associated with acid-base balance regulation, ion transport, and ammonia nitrogen excretion in the fish. This indicates that lncRNA regulation of gene expression plays an important role in the process of adaptation to high alkaline conditions in L. waleckii.